VALIDITY OF INSTRUMENT MEASURING SECONDARY SCHOOL STUDENTS LEARNING DIFFICULTIES IN PHYSIC EDUCATION - Imami, Muh Khairul Wajedi; Darus, Mazlina Mat; Zain, Zahida Aliatu; Hasyim, Mutahharah; Wahdah, Nurul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
In learning physic, students might experience learning difficulties that could hinder the knowledge transfer and the efficiency of the learning. It's caused by a limited number of instruments that are valid to measure students' learning difficulty in physical education. Therefore, the current research aims to validate physic learning difficulty scale for secondary school students in Indonesia. This research used a survey design. The current research participants were 388 students in Nusa Tenggara Barat, Indonesia. Two procedures were used to analyse the data: exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The results show that EFA with comprehensive techniques that compromise parallel analysis yielded a 3-factor solution: environment factor, metacognitive factor and emotional factor. The three factors solution was confirmed through CFA with the value: Chi Square=1.922, goodness of fit index (GFI)=.936, adjusted goodness of fit index (AGFI)=.913, Tucker–Lewis index (TLI)=.895, comparative fit index (CFI)=.913, root mean square error of approximation (RMSEA)=.049, and Standardized Root Mean Residual (SRMR)=.079. Therefore, based on psychometric analysis, the scale is valid and reliable to be used in measuring students physic learning difficulty of Indonesian secondary school students. The current research’s novelty is that it provides a valid and reliable instrument to measure student`s difficulty in physic education. The use of the current instrument can ensure the accuracy, reliability, and credibility of research related to student difficulty in physic education.